Kepemimpinan Pemuda dalam Pelestarian Sejarah Lokal : Analisis Peran Rio Tampati Putra sebagai Founder Museum Perang Sintuk - Naldi, Hendra; Najmi, Najmi; Silva, Ray; Veronika, Mutiara Rejani; Andeskoli, Oriza (Jurnal Kronologi, 2024)
This research is motivated by awareness of the important role of youth in preserving local history and culture. The Sintuk War Museum exists because of the enthusiasm of a young man from Nagari Sintuk named Rio Tampati Putra. Proving that youth leadership and initiative can be key in preserving and reviving local history. This research is qualitative research that uses historical research methods. Several stages in the Historiography process involve steps such as Heuristics (data collection), Verification (source criticism), Interpretation (interpretation), and historiography (historical writing). The results of this research show that Rio Tampati Putra's background in establishing the Sintuk War Museum was to teach the younger generation about the great struggle of Indonesia's ancestors in gaining independence. Through visionary and collaborative leadership, Rio Tampati Putra succeeded in making the Sintuk War Museum a source of historical learning for students and forming a community that is beneficial for the younger generation through collaboration with various parties.